2022
DOI: 10.1007/s10875-022-01272-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Testing in Egyptian Patients with Inborn Errors of Immunity: a Single-Center Experience

Abstract: Background Inborn errors of immunity (IEI) are a group of heterogeneous disorders with geographic and ethnic diversities. Although IEI are common in Egypt, genetic diagnosis is limited due to financial restrictions. This study aims to characterize the genetic spectrum of IEI patients in Egypt and highlights the adaptation of the molecular diagnostic methods to a resource-limited setting. Methods Genetic material from 504 patients was studied, and proper di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…Protein expression assays increased the spectrum of the diagnoses achieved and helped reach definitive diagnosis in several disorders like, DOCK8 deficiency, LRBA deficiency, XLA, CGD, Perforin deficiency, ADA deficiency, IL7RA deficiency, LADI and MHC-II deficiency [ 12 , 21 , 22 , 27 ]. Also, sending out for genetic testing has been cut down based on optimizing the molecular diagnosis strategy adapted in our center guided by the FCM [ 28 ]. Based on the FCM results, 744 patients (73%) were categorized and diagnosed with one of IEI disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Protein expression assays increased the spectrum of the diagnoses achieved and helped reach definitive diagnosis in several disorders like, DOCK8 deficiency, LRBA deficiency, XLA, CGD, Perforin deficiency, ADA deficiency, IL7RA deficiency, LADI and MHC-II deficiency [ 12 , 21 , 22 , 27 ]. Also, sending out for genetic testing has been cut down based on optimizing the molecular diagnosis strategy adapted in our center guided by the FCM [ 28 ]. Based on the FCM results, 744 patients (73%) were categorized and diagnosed with one of IEI disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The MENA cohort's higher rate of reported consanguinity, broader clinical spectrum and more systematic application of WES likely contributed to their overall higher diagnostic yield. However, our approach produced at least comparable yields to TGP-focused or mixed sequencing approaches applied to IEI-specific diagnostics in other resource-constrained settings [13,[141][142]. Some studies reported a smaller incremental gain in diagnostic yield from the addition of WES to TGPs [4,141], but ours was significantly higher.…”
Section: Many Of Our Index Patients Did Not Present With the Most 'Ca...mentioning
confidence: 68%
“…Patient had severe lymphopenia, hypogammaglobulinemia (low IgG and IgA), reduced CD3, CD4, CD8, CD19, CD56 and CD45RA, in addition to reduced all B cell subsets. This patient was diagnosed at a later stage by molecular genetic testing; Next generation sequencing (NGS) revealed homozygous mutation in NHEJ1 gene, con rming Cernunnos-XLF de ciency, a rare form of combined immunode ciency with typical presenting features [15].…”
Section: Laboratory Analysismentioning
confidence: 93%